Disorders/Differences of Sex Development Presenting in the Newborn With 46,XY Karyotype - Bertelloni, Silvano; Tyutyusheva, Nina; Valiani, Margherita; D'Alberton, Franco; Baldinotti, Fulvia; Caligo, Maria Adelaide; Baroncelli, Giampiero I.; Peroni, Diego G. (Frontiers in Pediatrics, 2021)
Differences/disorders of sex development (DSD) are a heterogeneous group of congenital conditions, resulting in discordance between an individual’s sex chromosomes, gonads, and/or anatomic sex. The management of a newborn with suspected 46,XY DSD remains challenging. Newborns with 46,XY DSD may present with several phenotypes ranging from babies with atypical genitalia or girls with inguinal herniae to boys with micropenis and cryptorchidism. A mismatch between prenatal karyotype and female phenotype is an increasing reason for presentation. Gender assignment should be avoided prior to expert evaluation and possibly until molecular diagnosis. The classic diagnostic approach is time and cost-consuming. Today, a different approach may be considered. The first line of investigations must exclude rare life-threatening diseases related to salt wasting crises. Then, the new genetic tests should be performed, yielding increased diagnostic performance. Focused imaging or endocrine studies should be performed on the basis of genetic results in order to reduce repeated and invasive investigations for a small baby. The challenge for health professionals will lie in integrating specific genetic information with better defined clinical and endocrine phenotypes and in terms of long-term evolution. Such advances will permit optimisation of counselling of parents and sex assignment. In this regard, society has significantly changed its attitude to the acceptance and expansion beyond strict binary male and female sexes, at least in some countries or cultures. These management advances should result in better personalized care and better long-term quality of life of babies born with 46,XY DSD.